Antioxidant activity of jambu bol [Syzygium malaccense (L.) Merr. and Perry] leaf extract - Al-Zabt, A.M.; Hamad, H.J.; Pak-Dek, M.S.; Ramli, N.S.; Rukayadi, Y. (Rynnye Lyan Resources, 2024)
Jambu bol [Syzygium malaccense (L.) Merr. and Perry] is well known to be used in folk medicine and reports are proving the biological activity of each part of this plant. This study aimed to determine the antioxidant activity of S. malaccense L. leaf extract. The methods used in this study were total phenolic content (TPC) assay, 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay, 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•) radical scavenging activity assay and ferric reducing antioxidant power (FRAP) assay. The results showed that the extract contained TPC of 44.10±0.06 mg GAE/g. The IC50 scavenging activities of DPPH and ABTS• were 0.0334 mg of Ascorbic acid E/g and 0.1352 mg of TE/g, respectively, while the antioxidant reducing power was 1013.50±0.07 mM Fe2+ / g. In conclusion, S. malaccense L. leaf extract was found to possess antioxidant activity, and this extract has potential to be developed to be used in food as a natural antioxidant agent.